HOMESICKNESS AND ACADEMIC ENGAGEMENT OF FIRST-YEAR OVERSEAS STUDENTS: THE ROLE OF LEARNING MOTIVATION AND ONLINE SOCIAL SUPPORT - Putri, Allychia Nanalingdita Thea; Tiatri, Sri; Beng, Jap Tji (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
The number of university students in Indonesia increases every year, and not all of them pursue education in their hometowns. Living far from family can trigger various psychological problems, such as homesickness, which may affect students’ academic engagement. This study aims to examine the mediating role of learning motivation and the moderating role of online social support (OSS) in the relationship between homesickness and academic engagement among first-year overseas students. A total of 158 first-year overseas students participated in this quantitative study with a moderated mediation model. Instruments used were UWES (academic engagement), UHS (homesickness), AMS (learning motivation), and OSSS (OSS). Data were collected online through Google Forms distributed via social media and analyzed using JASP with the Hayes PROCESS Macro, estimating 5,000 bootstrap samples. Results showed no relationship between homesickness and academic engagement, no relationship between homesickness and learning motivation, no mediating role of learning motivation in the relationship between homesickness and academic engagement, and no moderating role of online social support in the relationship between homesickness and learning motivation. However, it was found that there is a relationship between learning motivation and academic engagement. This study is expected to contribute to the development of educational psychology, especially regarding first-year overseas students, a population that remains under-researched.